Pewarisan Karakter Toleransi Aluminium Tanaman Sorgum Manis [Sorghum bicolor (L.) Moench] pada Stadia Bibit - Isnaini, Isnaini; Trikoesoemaningtyas, Trikoesoemaningtyas; Wirnas, Desta (Jurnal Agro Teknologi Tropika, 2014)
The objective of this research was to study the inheritance of Al tolerance of sweet sorghum at seedling stage. Thefour populations in this research were UPCA S1 (P1, susceptible parent) and Numbu (P2, tolerant parent), F1 and F1reciprocal and F2. The crosses of parental, F1, F1R and F2 generation were grown in University Farm of IPB and UPTDTenjo from June 2008 to June 2009. The study of Al tolerance inheritance in nutrient solution was conducted in greenhouse of University Farm of IPB from July-August 2009. Based on reciprocal analysis, all of characters are controlled bynuclear genes and their inheritance in not affected by maternal cytoplasm. The distribution of F2 genotype indicatedcontinuous with skewnesses which indicate that all characters are polygenics. All characters of Al tolerance in seedlingstage i.e. root length, root and shoot dry weight were controlled by additive gene action with contribution bycomplementary epistasis gene except shoot length that is controlled by additive gene action with duplicate epistasisgene. All characters had broad sense heritability from medium to high. Based on heritability value, pedigree selectionis the most effective selection method in breeding program for sorghum tolerance to Al.